Environmental effects on calving intervals in Nelore cows - Viana, Hildo Áurio; Ferreira, Paulo Roberto C. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of some environmental factors on 6.593 Nelore calving intervals were studied in the southwest region of Goiás State, Brazil. The following variables were determined: level of Nelore blood, calf sex, year and month of previous calving, and calving parity. The multiple regression analysis by the "stepwise" method was used. Only the three last variables did significantly affect the dependent variable (calving interval). The equation adjusted was: Ŷ = -390,82119 - 0,52908 Ø + 0,00899 Ø2 + 11,09659 A2 - 0,07557 A2 - 0,0609 M, where - calving order; A = year; M = month. From the total of 6,593 observations the average interval was 13,7 ± 0,056 months with CV- 33%. The year of previous calving determined a positive quadratic curve for intervals while the month and calving parity affected the intervals linearly in a negative way. Food and reproductive management seemed to explain the result obtained during a ten-year study.
Keywords: reproduction; management; environmental factors; parity